2019
DOI: 10.1038/s41431-019-0523-1
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the pathogenicity of c.2858G>T(p.(G953V)) in COL4A5 Gene: report of 19 Chinese families

Abstract: X-linked Alport syndrome (XLAS) is an inherited renal disease caused by mutations in COL4A5 gene. The c.2858G>T(p. (G953V)) in COL4A5 gene (rs78972735) has been considered pathogenic previously. However, there are conflicting interpretations of its pathogenicity recently. Here we presented 19 Chinese families, out of which 36 individuals (18 probands and 18 family members) carried the c.2858G>T(p.(G953V)) in COL4A5 gene. The clinical manifestations and genetic findings of them were analyzed. We found there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…21,[32][33][34] However, our recent gene analysis and reports from other groups have indicated that G953V is a single-nucleotide polymorphism variant and is nonpathogenic. 22 Consistent with those views, G953V exhibited the same trimer formation and secretion abilities as the wild type in our cell-based trimerization assay. We note that G953V is the only mutant without a significant difference in both N-and C-terminal trimer assays.…”
Section: G953vsupporting
confidence: 88%
“…21,[32][33][34] However, our recent gene analysis and reports from other groups have indicated that G953V is a single-nucleotide polymorphism variant and is nonpathogenic. 22 Consistent with those views, G953V exhibited the same trimer formation and secretion abilities as the wild type in our cell-based trimerization assay. We note that G953V is the only mutant without a significant difference in both N-and C-terminal trimer assays.…”
Section: G953vsupporting
confidence: 88%
“…The nature of other variants such as NM_000495.5:c.2858G>T (rs78972735; p.(Gly953Val)) in COL4A5 [ 55 ], and NM_000092.5:c.1634G>C (rs1800516; p.(Gly545Ala)) and NM_000092.4(COL4A4):c.2996G>A (rs13027659 p.(Gly999Glu)) in COL4A4 is less clear. All are very abundant in certain ancestries.…”
Section: Modification Of the Acmg/amp Criteria For The Col4a3–col4a5 Genes And Rationalementioning
confidence: 99%
“…All are very abundant in certain ancestries. p.(Gly953Val) is also located immediately adjacent to an interruption in the collagenous domain of the collagen IV α5 chain, but it is not on its own associated with haematuria, kidney failure or GBM lamellation [ 55 ], and has conflicting interpretations of pathogenicity in Clin Var (www.ncbi.nlm.nih.gov/clinvar/variation/24573/). Both p.(Gly545Ala) and p.(Gly999Glu) affect Gly residues within the collagenous domain of the collagen IV α4 chain itself.…”
Section: Modification Of the Acmg/amp Criteria For The Col4a3–col4a5 Genes And Rationalementioning
confidence: 99%
“…For example, missense variants that change Gly to another amino acid in COL4A5 are always considered to be pathogenic. However, p.Gly953Val is considered to be nonpathogenic [ 22 ] and p.Gly1000Val leads to a very mild phenotype resembling benign familial hematuria [ 23 ]. We are now attempting to reveal these differences using this approach.…”
Section: Triple Helix Formation Assaymentioning
confidence: 99%